Aqueous extract of Passiflora alata leaves modulates in vitro the indoleamine 2, 3-dioxygenase (IDO) and CD86 expression in bone marrow-derived professional antigen-presenting cells polarizing NOD mice T cells to a Treg profile. (April 2022) - Schumacher, Nayara Simon Gonzalez; Fernandes, Luís Gustavo Romani; de Lima Zollner, Ricardo
Highlights: Stressed MIN-6 cells as antigen source to BM p-APCs in NOD mice T cell activation. LAEPAL inhibit primed T cell proliferation and INF-γ, IL-6 and IL-10 production. LAEPAĹs polyphenols could induce tolerogenic APCs T cells to a Treg profile. Abstract: Dendritic cells (DCs) and macrophages are professional antigen-presenting cells (pAPCs), numerous in the pancreas of nonobese diabetic (NOD) mice and playing an essential role in the autoimmune response of type 1 diabetes. The expression of the enzyme indoleamine 2, 3-dioxygenase (IDO) is a critical factor for the tolerogenic activity of pAPCs, acting in the catabolism of tryptophan, providing metabolites that suppress the T cell effectors and induce T regulatory cells differentiation. Here we investigated the in vitro mechanisms of lyophilized aqueous extract from Passiflora alata leaves (LAEPAL) that modulates bone marrow-derived professional antigen-presenting cells (BM-pAPCs), affecting their ability to polarize T cells. A cell culture model was defined using mixed cultures of BM-pAPCs and T lymphocytes NOD mice with stressed MIN-6 cells as a source of pancreatic β cells antigens. We showed that the treatment with 300 µg/mL of LAEPAL induces a significant decrease in the CD4 and CD8 T effector lymphocytes proliferation from diabetic but not in non-diabetic mice, followed by a reduction of the IL-6 and IFN-γ cytokines release in the cell cultures supernatants. Moreover, we observed an increase of CD4 + CD25 + FoxP3 + Tregs in the cell cultures from diabetic mice. These results could be partially explained by the LAEPAL modulatory effects in BM-pAPCs, downregulating the CD86 co-stimulatory molecule expression, and increasing IDO-1 expression in F4/80+ BM-pAPCs. These results contribute to a better understanding of the polyphenols' immunomodulatory properties, meaning they could induce tolerogenic antigen-presenting cells, which could polarize T cells to a Treg profile and decrease the activity of CD4+ and CD8+ T effector cells.